Nest Relocation and Colony Founding in the Australian Desert Ant, Melophorus bagoti Lubbock (Hymenoptera: Formicidae) - Patrick Schultheiss; Sebastian Schwarz; Antoine Wystrach (Psyche: A Journal of Entomology)
Even after years of research on navigation in the Red Honey Ant, Melophorus bagoti, much of its life history remains elusive. Here, we present observations on nest relocation and the reproductive and founding stages of colonies. Nest relocation is possibly aided by trail laying behaviour, which is highly unusual for solitary foraging desert ants. Reproduction occurs in synchronised mating flights, which are probably triggered by rain. Queens may engage in multiple matings, and there is circumstantial evidence that males are chemically attracted to queens. After the mating flight, the queens found new colonies independently and singly. Excavation of these founding colonies reveals first insights into their structure.